Effects of structural steels microstructure and waveform on corrosion-fatigue behaviour of offshore wind turbine foundations. - Igwemezi, Victor Chinedu (Cranfield University, 2019)
Marine structures in the offshore environment are subjected to constant cyclic wave and wind forces. Also, the foundations are in direct contact with seawater (SW), hence introducing corrosion damage in the structure. Due to the cyclic loading cracks could nucleate and grow, or existing cracks could propagate at loads far less than the maximum design load, and the problem is worsened in marine environment. Offshore Wind Turbines (WTs) are relatively new structures and their long-term corrosion-fatigue performance data are very scarce. In fact, presently there are little or no public data on corrosion-fatigue performance of these sub-grades of S355 steel used in the design of extra-large (XL) Wind turbine support structures (WTSSs). This experimental research primarily seeks to understand the rate at which a crack grows in the modern normalised-rolled (NR) and thermomechanical control process (TMCP) S355 steel subgrades designated as S355G10+M, S355G8+M and S355J2+N under the influence of: fatigue waveforms, change in fatigue load level and material microstructure in seawater (SW) at frequencies within the range of commercial Wind Turbine (WT) operating condition. The test programme employed a soft-stiff frequency range of commercial WTs in the North Sea. The waveforms considered in this study are constant amplitude sinewave and trapezoid waveform (generally referred to here as hold-time) and the experiments were conducted under frequencies of 0.2Hz, 0.3Hz, 0.5Hz. The stress ratio in all tests was 0.1 and the maximum applied loads were 9kN and 10kN. All calculations where done under Linear Elastic Fracture Mechanics (LEFM) and all tests and investigations were limited to the Paris Region or the Stage II of the da/dN vs. ΔK plot, where LEFM applies. All the tests have been performed in accordance with BS 7910:2013+A1:2015 and ASTM E647-15. This study found that frequency has no obvious effect on the FCGR of ferrite-pearlite steels in air. There was enhancement of the FCGR in seawater by a factor that depended on the waveform and load level. The CFCGR of the sine waveform was found to be higher than that of the holdtime for all the load levels and frequencies used. Using the mean curve, SW enhanced the FCGR by an average factor of 1.48 under hold-time and 2.17 under sinewave throughout theParis Region in the range of 20 - 35 MPa√m with reference to the air mean curve. Similar trend was obtained if mean +2SD is used, giving an average factor of increase of 1.48 under hold-time and 2.30 under sinewave. Comparison of the experimental results on S355G8+M, S355G10+M and S355J2+N has shown that under both sinewave and hold-time waveforms, the CFCG trend in normalised steels (e.g. S355J2+N) is consistently higher than that of the TMCP steels (e.g. S355G8+M, S355G10+M) in both air and sea environments. Change in load level and frequency did not affect the CFCGR of the TMCP steels in SW under sinewave, but slight change was observed with decrease in the load level for the holdtime. The Pmax is found to have a profound influence on CFCGR than the cyclic frequency (in the range of 0.2Hz to 0.4Hz). Decreasing the load level reduces the effect of frequency in SW and the difference in CFCGR for waveforms diminishes with increasing frequency and ∆K. In SW, increase in the fatigue load and decrease in the frequency, especially for holdtime has the highest retarding effect under corrosion dominated regime. This is a consequence of what we referred to here as the microplastic zone size. High load level increases the microplastic zone size closest and ahead of the propagating crack tip and opens up the crack tip region to allow the entry of more damaging chemical species into the plastically deformed regions causing fast attack by the time-dependent corrosion process resulting to rapid crack tip dissolution and blunting. When the main active crack tip is blunted the crack propagation process is considerably reduced or even arrested for a very long time as observed especially for the hold time test. This appears to suggest that for same ∆K value, combination of low stress range and long crack length, a will be more damaging than combination of high stress and short a in SW. Corrosion products are also found to build up in and around the blunted crack tip leading to further retardation of the crack growth. Extensive blunting of the crack front due to availability of time explains why the CFCGR is generally lower in holdtime as compared to sinewave. Fractographic and metallographic analyses were carried out to understand the disparity in the CFCGR between the waveforms under the test conditions. Fractographic examination of the fractured surface of the corrosion-fatigue specimens showed that the CFCG mechanism is by ductile striations both in air and SW. The crack path was always non-planar with complex crack front. Generally, three phenomena were identified that primarily retarded crack growth in the ferrite-pearlite steels in air. These are crack diversion, crack bifurcation and metal crumbs. The three factors retarded the crack growth by reducing or re-distributing the effective driving stress at the main propagating active crack tips. It was found that the main crack tip blunting process is the primary factor controlling the CFCGR of steel at high ∆K and low frequency in a ferrite-pearlite steel in SW. Other fundamental factors are crack angle diversion, branching of crack front and formation of metal crumbs along the crack path. The extent of formation of the aforementioned phenomena is a strong function of the steel microstructure. This implies that microstructure has a strong effect on the FCGR of ferrite-pearlite steels in the Paris Region, both in air and SW. This conclusion is in contrary to current theory that microstructure has little or no effect in the Paris Region of the da/dN vs ∆K sigmoidal curve. Transgranular and quasi-intergranular modes of propagation in both environments were observed. The quasi-intergranular mode is a situation where the fatigue-crack propagated through a thin layer of high solute ferrite ribbon, 𝛼𝐻𝐴 adjacent to the low relief, αLR or the pearlite, P phases. The morphology and chemistry of the phases local to the main crack front and the load level appeared to determine which mode the crack growth would adopt. The angle the crack front made with the least resistant path ahead of it seemed to determine if it would propagate by transgranular or quasi-intergranular mode.
Keywords: Offshore wind turbine; monopile; fatigue; corrosion-fatigue; fatigue crack growth; microstructure; seawater; S355 steel; BS7910